2009
DOI: 10.1007/bf03346625
|View full text |Cite
|
Sign up to set email alerts
|

Iodine intake is still inadequate among pregnant women eight years after mandatory iodination of salt in Turkey

Abstract: Our study revealed that iodine deficiency still remains a serious problem for pregnant women. Based on our results, antenatal follow-up protocols in the primary care setting in Turkey must include iodine supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 12 publications
2
27
1
1
Order By: Relevance
“…Nevertheless, many studies have shown an inverse relationship between neonatal TSH and maternal urinary iodine concentration, supporting the notion that the frequency of neonatal TSH concentrations >5 µU/mL was a sensitive indicator of iodine nutrition during pregnancy (39,40,41). In recent years, several studies have already demonstrated insufficient iodine intake of pregnant women living in different regions of Turkey (17,18), including apparently iodine-sufficient areas (19). As a result, the finding of the high frequency of transient CH is in line with the high recall rate in the NNSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many studies have shown an inverse relationship between neonatal TSH and maternal urinary iodine concentration, supporting the notion that the frequency of neonatal TSH concentrations >5 µU/mL was a sensitive indicator of iodine nutrition during pregnancy (39,40,41). In recent years, several studies have already demonstrated insufficient iodine intake of pregnant women living in different regions of Turkey (17,18), including apparently iodine-sufficient areas (19). As a result, the finding of the high frequency of transient CH is in line with the high recall rate in the NNSP.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of transient CH in Turkey is much higher than the expected rate of 5-10% reported for iodine-sufficient populations (14). Numerous studies carried out in newborns (15,16,17) and pregnant women (18,19,20) have already demonstrated that iodine deficiency is a continuing problem of Turkey. Also, a recent study revealed that iodine excess could be a problem in newborns due to use of iodine-containing antiseptics during delivery despite maternal iodine deficiency (20).…”
Section: Introductionmentioning
confidence: 99%
“…The public health strategy to minimize iodine deficiency is salt iodization; in Turkey salt iodization become mandatory in 1998 [13], [14]. Despite these efforts to fortify the population through iodized salt, some populations in Turkey appear to remain iodine deficient [15], [16]. For example, a recent study found low iodine intakes in two cities in Turkey (Burdur [near Isparta] and Kayseri) [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Erdogan MF et al [15] found median UIC 89 μg/L in nonsurgical hospital stuff in in Ankara in a recent study. Kut A et al [16] found iodine deficiency in 49, 6% of Turkish first trimester pregnant women in Adana. Oguz Kutlu A, et al [17] found iodine deficiency in 72, 8% of Turkish second trimester pregnant women in Ankara.…”
Section: Discussionmentioning
confidence: 98%